INSPIRING THE SOUL: HOW TEACHERS ENHANCE SPIRITUAL INTELLIGENCE IN STUDENTS - Saputra, Andika Ari; Fatimah, Sunnilam; Ehwanudin, Ehwanudin; Muslihati, Muslihati; Reba, Yansen Alberth; Arizona, Arizona; Kusumaningtyas, Wahyu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:The role of teachers or educators in motivating students' spiritual intelligence is quite good, enthusiasm in implementing school regulations and continues to develop, marked by good behavior carried out by students at school and polite speech in speaking and respecting parents, through good habits. Both of these are very helpful in increasing spiritual intelligence motivation. Students are directed to pray the Sunnah Duha prayer, recite the Koran, memorize it, and are always given good advice and to always be enthusiastic about learning so that they get used to it. This is done so that the faith in students is instilled in doing good deeds and good habits in everyday life, at home and at the madrasah so that they can learn to be good children and respect their parents.